Fluoroquinolone resistance protein NorA of Staphylococcus aureus is a multidrug efflux transporter. - Neyfakh, A A (1993)
The gene of the Staphylococcus aureus fluoroquinolone efflux transporter protein NorA confers resistance to a number of structurally dissimilar drugs, not just to fluoroquinolones, when it is expressed in Bacillus subtilis. NorA provides B. subtilis with resistance to the same drugs and to a similar extent as the B. subtilis multidrug transporter protein Bmr does. NorA and Bmr share 44% sequence similarity. Both the NorA- and Bmr-conferred resistances can be completely reversed by reserpine.